Electricity Availability, Human Capital Investment and Sustainable Economic Growth Causality in Sub Sahara Africa: Revisited Evidences - Musibau, Hammed Oluwaseyi; Mahmood, Suraya; Ismail, Suraya; Haruna, Muhammad Aminu; Khan, Muhammad Umair (International Journal of Energy Economics and Policy, 2019)
The paper examines the impact of electricity availabilities proxy by electricity supply, human capital development and the role of institutional qualities on economic growth in Sub-Sahara African countries using a panel data spanning from 1980 to 2016. The study utilized various dynamic panel models (Dynamic Ordinary Least Square, DOLS, PMG, DFE and FMOLS) and several panel unit roots model were adopted to check the degree of integration of the variables. Our empirical results found that electricity consumption, electricity availability and control of corruption have a positive impact on economic growth in SSA countries. However, human capital development has a negatively significant impact on economic growth in SSA countries. A deregulated energy sector is likely to yield smaller net benefits than a regulated market due to nature of African economies due to the level of corruption in the region. We therefore suggest a policy to improving their institutions qualities and build a good political structure to utilities government expenditure on electricity supply and human capital development to ensure economic growth in SSA countries. Keywords: Electricity availability, Institutional qualities, Human Capital development and Sub-Sahara Africa. JEL Classifications: K32 H52, F43, R11 DOI: https://doi.org/10.32479/ijeep.8201